Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18203/2319-2003.ijbcp20171109
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of methyldopa and labetalol in controlling blood pressure in hypertensive disorders of pregnancy

Abstract: Background: Hypertensive disorders represent the most common medical complication of pregnancy, with a reported incidence of 6-10% and accounts for 15% of maternal mortality. Effective management of pregnancy induced hypertension is vital to improve maternal and foetal outcomes. As data are scarce on comparison of labetolol and methyldopa this study was undertaken. The objective of present study is compare the efficacy and safety of Labetalol versus Methyldopa in the management of Mild to Moderate pregnancy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Another study showed both drugs to be comparable in control of blood pressure in pregnancy induced hypertension. However spontaneous onset of labour was significantly more in patients who used labetalol 11 . Our study has done comparison between labetalol and methyldopa only in achieving better control of blood pressure.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Another study showed both drugs to be comparable in control of blood pressure in pregnancy induced hypertension. However spontaneous onset of labour was significantly more in patients who used labetalol 11 . Our study has done comparison between labetalol and methyldopa only in achieving better control of blood pressure.…”
Section: Discussionmentioning
confidence: 84%
“…-------------------------------------------------------------------------------Received on 11-04-2021 Accepted on 22-08-2021 A meta-analysis conducted to compare the efficacy and safety profile of alpha methyldopa and labetalol concluded that labetalol has better control of blood pressure in pregnancy and has less side effects than alpha methyldopa 10 . Another trial, conducted to compare efficacy of methyldopa and labetalol concluded that both have equal efficacy in controlling mean systolic blood pressure 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Nifedipine is a calcium channel blocker which is effective at reducing blood pressure without uteroplacental blood flow nor slowing foetal heart rate [ 24 ]. While methyldopa is preferred because it is a centrally acting α -agonist that decreases sympathetic outflow to decrease BP, it has a very long duration of action and the best safety profile amongst the antihypertensive drugs used during pregnancy [ 25 ]. Currently methyldopa has no associated congenital anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…15 In the study conducted by Dharwadkar et al the mean age of patients for Methyldopa group was 25.95±3.94 years and for Labetalol group was 26.65±3.73 years 16. In a study conducted by Pentareddy et al, the mean age of the patients in the Methyldopa group was 22.3 years while it was 23.23 years in Labetalol group and both groups were statistically comparable 17.…”
mentioning
confidence: 90%